A Measurement model of teacher's efficacy in teaching Arabic - Mohamed Adnan, Mohamad Azrien; Mamat , Arifin; Ahmad Mohamed, Ismaeil Hassanein; Ibrahim, Mohd Burhan; Jumahat, Tajulashikin (2015)
Teachers’ sense of efficacy is an essential construct in teaching and learning. Researchers in education have recognized that teacher efficacy has strong relationship with various aspects of teaching and learning. This study aims at 1) examining the construct of teachers’ sense of efficacy and 2) evaluating the adequacy of the teachers’ sense of efficacy measure across teachers’ gender. In so doing, this study attempt to develop the extent to which the conceptualized teachers’ sense of efficacy measure reproduces the data. The data were collected from adopted version of Teachers’ Sense of Efficacy Scale (TSES) by Tschannen-Moran and Woolfolk Hoy (2001) administered to 236 teachers of National Religious Secondary School in Malaysia. The results of confirmatory factor analysis supported the adequacy of teacher’s sense of efficacy measure and found that teacher’s sense of efficacy is a multidimensional construct with four underlying dimensions namely efficacy for language use, efficacy for classroom management, efficacy for teaching strategies and efficacy for student engagement. The measurement model also found to be applicable across gender.